Two Marias (Brig) records - Two Marias (Brig)
Congressional agreement (1790 January 4) concerning the regulation of seamen in merchant service; receipt (1810 March 3 and May 12) signed by Elisha Doane, master seaman; and list of crew members (1810 March 7).
Merchant vessel sailing out of Boston, Mass.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Doane, Elisha, -- -1848.; Merchant marine -- Massachusetts -- Boston; Sailors -- Legal status, laws, etc. -- United States; Ship's papers -- 18th century; Ship's papers -- 19th century